Neopharyngeal Stricture following Laryngectomy - Hanubal, Krishna S.; Chheda, Neil N.; Dziegielewski, Peter T. (Seminars in Plastic Surgery, 2022)
Stricture formation is a serious complication following pharyngeal reconstruction. These strictures can be life-threatening and can severely impact quality of life. In this article, the existing literature on surgical risk factors linked to neopharyngeal stricture formation is reviewed. Intraoperative preventative measures reconstructive surgeons should consider are also discussed. Finally, this article will describe the evaluation and management of pharyngoesophageal strictures, including the challenges and options when dealing with refractory strictures.
Keywords: laryngectomy; head and neck reconstruction; stricture